2020
DOI: 10.3390/molecules25081888
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rosa canina Fruits Collected in Urban Areas of Slovakia. Genome Size, iPBS Profiles and Antioxidant and Antimicrobial Activities

Abstract: The studies of plant bacterial endophytes, colonizing the plant tissues without any signs of diseases, are essential for understanding of ecological interactions. The aim of our study is to detect microbiological contamination and to assess the antimicrobial, antioxidant activity, total phenolic, carotenoid content, genome size, and ploidy of non-cultivated Rosa canina sampled from urban areas. Samples of Rosa canina fruits were collected in three locations in Slovakia. The highest total viable count and the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Oxidative stress can be reduced by providing antioxidant compounds to the diet. Plants are a widely reported source of antioxidants [ 49 , 50 , 51 , 52 ]. Edible insects, in addition to basic nutrients, also provide biologically active compounds, including antioxidants, but also anti-nutritional compounds, such as phytic acid, saponins, oxalates, and tannins.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress can be reduced by providing antioxidant compounds to the diet. Plants are a widely reported source of antioxidants [ 49 , 50 , 51 , 52 ]. Edible insects, in addition to basic nutrients, also provide biologically active compounds, including antioxidants, but also anti-nutritional compounds, such as phytic acid, saponins, oxalates, and tannins.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Hassan et al [52] noticed that Quillaja saponis were toxic against Salmonella typhimurium, Staphylococcus aureus. What is more, plant extracts are widely investigated as preservatives in foods because of their ability to inhibit bacteria growth [53,54]. Some authors reported bacteriostatic and antifungal properties depending on essential oils preparation [55][56][57].…”
Section: Emulsions' Biological Activitymentioning
confidence: 99%
“…The analysis was performed with a Microflex LT (Bruker Daltonics, Bremen, Germany) instrument and Flex Control 3.4 software and Biotyper Realtime Classification 3.1 with BC specific software. Confidence scores of ≥2.0 and ≥1.7 were the criteria for successful identification at the levels of species and genus, respectively [ 70 ].…”
Section: Methodsmentioning
confidence: 99%